Yield gap analysis and entry points for improving productivity on large oil palm plantations and smallholder farms in Ghana. (September 2018) - Rhebergen, Tiemen; Fairhurst, Thomas; Whitbread, Anthony; Giller, Ken E.; Zingore, Shamie
Abstract: Oil palm production must increase in Ghana to meet the increasing demand for palm oil and avoid costly imports. Although maximum fruit bunch (FB) yields of >20 t ha −1  yr −1 are achievable, average FB yields in Ghana are only 7 t ha −1  yr −1 . Despite the pressing need to increase palm oil production and improve yields, knowledge of the underlying causes of poor yields in Ghana is lacking. Closing yield gaps in existing plantings in smallholdings and plantations offers great opportunities to increase oil production without area expansion, thus sparing land for other uses. This study sought to understand the magnitude and underlying causes of yield gaps in plantation and smallholder oil palm production systems in Ghana based on a detailed characterization of management practices and yield measurements over a two-year period. Using a boundary line analysis, the water-limited yield (Yw) over a planting cycle was defined as about 21 t ha −1  yr −1 FB, with yield gaps of 15.4 t ha −1  yr −1 FB at smallholder farms and 9.8 t ha −1  yr −1 FB at plantations. Poor management practices, including incomplete crop recovery (i.e., harvesting all suitable crop) and inadequate agronomic management were the main factors contributing to these yield gaps. Productivity losses were further exacerbated by low oil extraction rates by small-scale processors of 12% as compared to 21% by the large-scale processors. The potential losses in annual crude palm oil (CPO) during the crop plateau yield phase therefore exceed 5 and 3 t ha −1  yr −1 for small-scale and large-scale production systems respectively. Investment to reduce yield gaps by appropriate agronomic and yield recovery practices across all production systems, while improving access of smallholder producers to more efficient oil palm processing facilities, can make a significant contribution to closing the supply gap for palm oil in Ghana. The impact of such investments on large-scale plantations could result in a doubling of CPO production. Smallholder farmers could benefit the most with a fourteen-fold increase in CPO production and economic gains of >1 billion US$. Highlights: Analysis of various causes of yield gaps and its quantification in oil palm production systems in Ghana. Application of boundary line analysis to estimate the water limited yield (Yw) over a planting cycle of oil palm. Incomplete crop recovery and poor agronomic management are the main factors contributing to the yield gaps. Productivity losses are further exacerbated by poor oil extraction rates at small-scale and large-scale processors.